Formulation and Stability of Miana Leaf Extract Spray Gel with Antioxidant - Nelly Suryani; Rachmadi Wibowo; Rosa Adelina; Vivi Anggia; Tania Sabarini; Sabrina Dahlizar; Ofa Suzanti Betha; Estu Mahanani Dhilasari (ALCHEMY Jurnal Penelitian Kimia, 2026)
The extract of Miana leaves (Coleus scutellarioides L.) is recognized for possessing potent antioxidant Action. This research aimed to develop a physically stable spray gel incorporating miana leaf extract and to evaluate its antioxidant potential through the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. Three formulations with different proportions of Carbopol and hydroxypropyl methylcellulose (HPMC) were evaluated for stability under room-temperature storage and during cycling tests, with organoleptic characteristics and viscosity as assessment parameters. The extract alone exhibited very strong antioxidant Action (IC₅₀ = 47.71 ppm). In comparison, the spray gel formulations showed IC₅₀ values of 141.18 ppm (FE1, 1%), 113.72 ppm (FE2, 3%), and 80.90 ppm (FE3, 5%), corresponding to moderate, moderate, and strong Action, respectively. Among these, FE2 (3% extract) demonstrated the most favorable physical stability.